2012
DOI: 10.1016/j.psc.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodevelopmental Hypothesis of Schizophrenia

Abstract: The neurodevelopmental hypothesis of schizophrenia suggests that the disruption of early brain development increases the risk of later developing schizophrenia. This hypothesis focuses attention on critical periods of early brain development. From an epidemiologic perspective, various prenatal and perinatal risk factors have been linked to schizophrenia, including exposures related to infection, nutrition, and obstetric complications. From a genetic perspective, candidate genes have also been linked to altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 124 publications
2
22
0
Order By: Relevance
“…The pathogeneses of schizophrenia and other complex neuropsychiatric disorders are likely rooted in aberrant neurodevelopment (Lewis and Levitt, 2002; Piper et al, 2012; Rapoport et al, 2012). Environmental disturbances during pregnancy may interact adversely in genetically predisposed offspring to compromise neuronal circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogeneses of schizophrenia and other complex neuropsychiatric disorders are likely rooted in aberrant neurodevelopment (Lewis and Levitt, 2002; Piper et al, 2012; Rapoport et al, 2012). Environmental disturbances during pregnancy may interact adversely in genetically predisposed offspring to compromise neuronal circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most explored aspects on the environment-gene interaction prompting schizophrenic phenotype is the impact of harsh early life conditions, leading to the neurodevelopmental hypothesis of schizophrenia (Fatemi and Folsom, 2009; Piper et al, 2012), which postulates that neurochemical disturbances induced by adverse early life events could permanently affect brain function, producing abnormalities that would ultimately underlie the emergence of the disorder. The early stages of life are characterized by an intense neural development, in which there is a dynamic process of synaptic shaping and pruning, making this period highly vulnerable to damaging disturbances (Martínez-Téllez et al, 2009; Stolp et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many SCZ putative risk genes are expressed prenatally or early in pluripotent stem cell (PSC) differentiation [2628], highlighting the importance of studying developmental process to clarify the etiology of SCZ. Many genetic as well as environmental models of SCZ show more pronounced SCZ-like behavioral and morphological changes with perturbations during early development, indicating the significance of developmental disturbance in generating SCZ-like abnormalities [2932]. However, the ability to study these critical pathologic events in the developing human nervous system once seemed unimaginable since after symptom onset in young adulthood, it is not possible to go back in time to study what happened during fetal brain development (Fig.…”
Section: Developmental Model For Schizophreniamentioning
confidence: 99%
“…Srikanth et al [32] reported that DISC1 NPCs show an abnormal forebrain specification and high levels of Wnt signaling accompanied by increased neural proliferation, which could be reversed by early inhibition of Wnt. Wen et al [41] examined the mature neuronal phenotype and observed a synaptic release deficit using 90% homogeneous glutamatergic neuronal population, which was reversed by isogenic correction of DISC1 mutation.…”
Section: Recent Ipsc-based Cellular Models Of Sczmentioning
confidence: 99%